2014
DOI: 10.1016/s1470-2045(14)70030-0
|View full text |Cite
|
Sign up to set email alerts
|

Dovitinib versus sorafenib for third-line targeted treatment of patients with metastatic renal cell carcinoma: an open-label, randomised phase 3 trial

Abstract: Summary Background An unmet medical need exists for patients with metastatic renal cell carcinoma (RCC) who have progressed on a vascular endothelial growth factor (VEGF)–targeted therapy plus a mammalian target of rapamycin (mTOR) inhibitor. Fibroblast growth factor (FGF) pathway activation has been proposed as a mechanism of escape from VEGF-targeted therapies. Dovitinib is an oral tyrosine kinase inhibitor that inhibits VEGF and FGF receptors. This open-label, multicenter phase 3 study compared dovitinib w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(170 citation statements)
references
References 27 publications
1
161
1
7
Order By: Relevance
“…In the INTORSECT trial, comparing the effectiveness of sorafenib versus temsirolimus in the second-line treatment setting, no significant difference was noted between temsirolimus and sorafenib on progression-free survival but an overall survival advantage was reported for sorafenib in the second-line setting 12 . In a parallel trial, no statistically significant difference was found between sorafenib and dovitinib in a third-line treatment setting 13 . However, outcomes of second-line mTOR and TKI treated patients in the community setting have not been extensively explored.…”
Section: Introductionmentioning
confidence: 97%
“…In the INTORSECT trial, comparing the effectiveness of sorafenib versus temsirolimus in the second-line treatment setting, no significant difference was noted between temsirolimus and sorafenib on progression-free survival but an overall survival advantage was reported for sorafenib in the second-line setting 12 . In a parallel trial, no statistically significant difference was found between sorafenib and dovitinib in a third-line treatment setting 13 . However, outcomes of second-line mTOR and TKI treated patients in the community setting have not been extensively explored.…”
Section: Introductionmentioning
confidence: 97%
“…Despite positive phase 2 data with this drug, 15 the GOLD study failed to show any improvement in outcomes with dovitinib. 16 Other data from phase 3 trials suggest the potential use of approved second-line agents in the third-line setting. In the RECORD-1 trial, 26% of patients had undergone treatment with two prior anti-VEGFR-TKIs and demonstrated a similar PFS benefit with everolimus to the overall population.…”
Section: Third-line Treatmentmentioning
confidence: 99%
“…Dovitinib, a TKI that targets FGFR, PDGRF and VEGFR, [17] failed in demonstrating a progression-free survival (PFS) and overall survival advantage over sorafenib in the third-line setting after progression to VEGFR and mTOR inhibitors, not corroborating the strong preclinical rational of targeting the FGF pathway critical for antiangiogenic escape. [18] The main criticism of this phase 3 study (the GOLD trial) lies in the inappropriate timing of FGF inhibition (immediately after failure of an mTOR inhibitor). [19] During mTOR inhibition treatment, in fact, cancer cells could restore a VEGF-driven angiogenesis (rather than FGF), given the temporary effects of VEGF-inhibitor resistance.…”
Section: Emerging Fgf/fgfr Inhibitorsmentioning
confidence: 99%